Problematik Kewenangan Pengadilan Agama dalam Menangani Perkara Waris - Ramli, Mohammad (Prodi HKI IAI Miftahul Ulum Pamekasan, 2023)
The Religious Court is a special judicial institution that handles and decides cases of Muslims based on the principles of Islamic personality. The absolute competence of the Religious Courts is stated in Article 49 of Law Number 7 of 1989, namely that the Religious Courts have the duty and authority to examine, decide and resolve cases at the first level between Muslims in the fields of (a) Marriage, (b) inheritance, wills and gifts made based on Islamic law (c) waqf and shadaqah. Based on Law Number 7 of 1989, the Religious Court has absolute authority in inheritance cases. Inheritance cases can take the form of lawsuits and petitions. However, in reality, religious courts have not been optimal in exercising this authority. This can be seen from the lack of inheritance cases decided by religious courts. These problems are partly due to the still entrenched customary inheritance law in Indonesian Muslim society, making it allergic to resolving inheritance problems in the Religious Courts. Moreover, some advocates also seem reluctant to refer their clients' inheritance cases to the Religious Courts.